The slave dancer - Fox, Paula (Aladin Paperbacks, 2008)
Kidnapped by the crew of an Africa-bound ship, a thirteen-year-old boy discovers to his horror that he is on a slaver and his job is to play music for the exercise periods of the human cargo.